2017
DOI: 10.1111/add.13747
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of heroin use: 10–11‐year findings from the Australian Treatment Outcome Study

Abstract: Long-term trajectories of heroin use in Australia appear to show considerable heterogeneity during a decade of follow-up, with few risk factors predicting group membership. Just more than a fifth continued to use at high levels, while fewer than a fifth become abstinent early on and remained abstinent. The remainder showed fluctuating patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 46 publications
5
28
0
Order By: Relevance
“…This implies that consumption's trajectories are in fact non explosive, and they will converge to a stationary level of consumption. As observed in the introduction, this outcome is consistent even with the observed individual consumption trajectories of goods that are commonly considered strongly addictive such as, e.g., heroin, crack and cocaine (Hser et al, 2008;Teesson et al, 2017). The finding that the coefficient on future price (φ 3 ) is different from 0 provides evidence in favor of a forward looking behavior of agents.…”
Section: An Application To Smokingsupporting
confidence: 83%
See 1 more Smart Citation
“…This implies that consumption's trajectories are in fact non explosive, and they will converge to a stationary level of consumption. As observed in the introduction, this outcome is consistent even with the observed individual consumption trajectories of goods that are commonly considered strongly addictive such as, e.g., heroin, crack and cocaine (Hser et al, 2008;Teesson et al, 2017). The finding that the coefficient on future price (φ 3 ) is different from 0 provides evidence in favor of a forward looking behavior of agents.…”
Section: An Application To Smokingsupporting
confidence: 83%
“…The theoretical advantage is that this demand function does not feature explosive dynamics. This implies that temporary shocks will be dampened over time and that consumption will tend toward a stationary level, a prediction that is consistent with the empirical observation that consumers of addictive goods typically converge to stable consumption levels (Hser et al, 2008;Teesson et al, 2017). The empirical advantage is that, under assumptions typically used in the literature, the demand for an addictive good can be represented by a linear first-order difference equation.…”
Section: Introductionsupporting
confidence: 64%
“…Heroin, also known as diethylmorphine, is a semi‐synthetic opioid derived from morphine and together with abuse of pharmaceutical opioids, contributes to the largest proportion of the global burden of disease of all illicit drugs . This is due to the high mortality and morbidity correlated with injected heroin use including infective endocarditis and hepatitis, but also the other associated harms including overdose, blood‐borne virus transmission and associated crime makes heroin use a serious public health problem .…”
Section: Opioids – Heroin and Methadonementioning
confidence: 99%
“…For instance, research has found that different drug types carry with them different social meanings (Allen & Alberici, 2018;Hughes, Lancaster, & Spicer, 2011;Shapiro, 2002;Taylor, 2008) and these social meanings are often expressed and experienced by users of these substances in different ways. In Australia, heroin has long been considered a highly problematic and addictive drug (Teesson et al, 2017) and the image of a 'dependent heroin user' has largely been fuelled by pejorative imagery and negative stereotypes, both in media (Hughes et al, 2011;Taylor, 2008) and in film (Allen & Alberici, 2018). The social narrative surrounding regular heroin use as the last drug in a continuum of drug severity (Teesson et al, 2017) has also fuelled the idea that to use heroin is to be dependent.…”
Section: Primary Drug Typesmentioning
confidence: 99%
“…In Australia, heroin has long been considered a highly problematic and addictive drug (Teesson et al, 2017) and the image of a 'dependent heroin user' has largely been fuelled by pejorative imagery and negative stereotypes, both in media (Hughes et al, 2011;Taylor, 2008) and in film (Allen & Alberici, 2018). The social narrative surrounding regular heroin use as the last drug in a continuum of drug severity (Teesson et al, 2017) has also fuelled the idea that to use heroin is to be dependent. What this means for regular heroin users, then, is that this social narrative and the consequences that flow from it, are likely internalised by these individuals as socially constructed and structured experiences of dependency.…”
Section: Primary Drug Typesmentioning
confidence: 99%